Penyuluhan Hukum Tentang Kenakalan Remaja di Era Digitalisasi - Kusumaningsih, Rila; Rida Ridiawati (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Teenagers in this era of digitalization are increasingly behaving defiantly from existing rules and norms. It cannot be denied that increasingly sophisticated technology has a big influence on the problem of increasing juvenile delinquency in the era of digitalization. Various internal and external factors can trigger juvenile delinquency, especially the lack of existing knowledge and lack of support and relationships from both parents and teachers at school. Guidance from parents and the environment regarding juvenile delinquency can be an important role to increase awareness and provide insight to build good attitudes and not be easily influenced by juvenile delinquent behaviour. The objective of this activity is to educate students about the dangers of juvenile delinquency, raise awareness about its negative impacts, and equip them with the knowledge and skills to make better decisions in their daily lives. The method used in this activity is direct counselling to students at Rajapolah Middle School. The results and conclusions of this counselling are to provide insight and form a firm attitude and not easily fall into doing negative things to students at Tasikmalaya Middle School regarding preventing juvenile delinquent behaviour through understanding and knowledge regarding the bad impacts that can result from juvenile delinquent behaviour.